2009
DOI: 10.1143/jjap.48.015501
|View full text |Cite
|
Sign up to set email alerts
|

Ni Oxyhydroxide Thin Films Prepared by Reactive Sputtering Using O2 + H2O Mixed Gas

Abstract: In this study, we have examined the preparation of thin films of Ni oxyhydroxide, which are used for batteries, supercapacitors, and electrochromic devices, by reactive sputtering. Transmittance and resistivity were found to decrease with the incorporation of H 2 O into the sputtering gas. This indicates that the valence state of Ni atoms in the film changes from Ni 2þ to Ni 3þ . Peaks due to Ni-OH and hydrogen bonded OH were observed by Fourier transform IR (FTIR) spectroscopy of the films sputtered in O 2 þ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…To allow for a uniform application of the circuit in Figure , a measurement window (10 kHz to 0.1 Hz) was chosen that would exclude the loop related to film resistance and capacitance. On the basis of the resistivities of Ni­(OH) 2 /NiOOH (10 1 –10 6 Ω cm –1 ) and FeOOH (10 5 –10 7 Ω cm –1 ), ,, the film thickness (7 nm), the film area (0.2 cm –2 ), and a reasonable estimate of the film capacitance (0.1–10 μF cm –2 ), , we estimate that the RC time constant of this loop should lie outside the measurement window and contribute little to the 10 kHz to 0.1 Hz range, though we cannot exclude some contribution to R-Ω from this loop. As we show below, this assumption is valid, as no feature in the Nyquist or phase plot is observed that can be assigned to an RC component related to the film resistance and capacitance.…”
Section: Resultsmentioning
confidence: 93%
“…To allow for a uniform application of the circuit in Figure , a measurement window (10 kHz to 0.1 Hz) was chosen that would exclude the loop related to film resistance and capacitance. On the basis of the resistivities of Ni­(OH) 2 /NiOOH (10 1 –10 6 Ω cm –1 ) and FeOOH (10 5 –10 7 Ω cm –1 ), ,, the film thickness (7 nm), the film area (0.2 cm –2 ), and a reasonable estimate of the film capacitance (0.1–10 μF cm –2 ), , we estimate that the RC time constant of this loop should lie outside the measurement window and contribute little to the 10 kHz to 0.1 Hz range, though we cannot exclude some contribution to R-Ω from this loop. As we show below, this assumption is valid, as no feature in the Nyquist or phase plot is observed that can be assigned to an RC component related to the film resistance and capacitance.…”
Section: Resultsmentioning
confidence: 93%
“…Devices incorporating W-oxide-based and Nioxide-based films have attracted much interest [21], and EC -smart windows‖ using this combination of materials are currently introduced on the market [10]. However, the Ni-oxidebased films are still in need of refinement, and research on Ni-oxide-based films is pursued vigorously; recent (2009 and later) studies have been published on such films prepared by evaporation [22], sputtering [23][24][25][26][27], chemical vapor deposition [28], various wet-chemical techniques such as sol-gel deposition [29][30][31][32][33][34][35][36] and chemical bath deposition [37][38][39][40][41][42][43][44], and electrodeposition [44][45][46][47][48][49]. Electrochromic Ni-oxide-based films have been made also by electrophoretic deposition of Ni hydroxide nanoparticles [50] and from Ni oxide pigments deposited from water dispersion [51].…”
Section: Introductionmentioning
confidence: 99%
“…The scanning electron microscopy (SEM) image confirms the well-retained sheet morphology of lithiated NiO (Figure S3c). NiO was reported to be thermodynamically unstable under electro-oxidation conditions, and stable NiOOH could be formed on its surface . Nevertheless, the phase structure of NiOOH derived from NiO is unexplored.…”
mentioning
confidence: 99%
“…NiO was reported to be thermodynamically unstable under electro-oxidation conditions, and stable NiOOH could be formed on its surface. 28 Nevertheless, the phase structure of NiOOH derived from NiO is unexplored. Herein, after in situ reconstruction, the lithiated NiO reconstructs to NiOOH, which displays a sheet structure assembled by the smaller nanosheets (Figures 1a and S3d).…”
mentioning
confidence: 99%